Tradição e ruptura: Pierre Boulez e a formação do cânone no pós-guerra (1946-1954) - Rizek, João Gabriel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The concepts of Canon and Tradition are of the most importance inside the artistic debate. Not only they shape our understanding of what music should be but also what we take as being classical music. Their mechanisms help us shape practices and transform what we take as being theories. Through the investigation of the canon’s mechanisms, as exemplified by several notions ranging from musicology, philosophy and literary criticism, we will investigate in this dissertation how one particular canon took shape. It has to do with the music being created and played in the Post-war period, that is, serialism. Far from being the only music composed in those years, Pierre Boulez, among several musical institutions and publications, took every measure to guarantee its power among all the other artistic languages. We will analyze here how Boulez defended that music, being responsible for the dimension it has achieved in those years. In order to do that we will investigate more accurately Boulez’s essays collected in Stocktakings from an Apprenticeship. As we will see, far from being an arbitrary solution, the manipulation of the canon has political implications, responsible for what governs our ways of understanding and practicing music.

Dentro do âmbito artístico, os conceitos de cânone e tradição são basilares. São eles os responsáveis por orientar e restringir desde a prática até a concepção daquilo que tomamos por música clássica. Seus mecanismos moldam a prática e transformam a teoria. A partir do exame destes conceitos, tal como entendidos por uma seleção de abordagens advindas da musicologia, da filosofia e da teoria literária, investigaremos nesta dissertação como se formou um determinado cânone. Trata-se daquele pensado pelos compositores surgidos no pós-guerra europeu, sobretudo nos anos de 1946 a 1954. Encabeçados por Pierre Boulez, instituições musicais e compositores, publicações editoriais e programas de orquestra pareciam apontar apenas para um tipo de música: a música serial. Analisaremos aqui como Boulez a defendeu e mobilizou forças para que ela se tornasse a poética mais comentada e praticada nos anos seguintes à Segunda Guerra. Para tanto, analisaremos sobremaneira os textos contidos na sua coletânea de ensaiosApontamentos de Aprendiz. Como veremos, longe de ser uma postura arbitrária, a tentativa de manipulação do cânone levada a cabo por uma série de atores torna-se uma medida política, praticada por aqueles que possuem concepções e determinações do que a música, sua prática e o seu entendimento devem ser.
Keywords: Boulez, Pierre, 1925-; Cânone (Música); Politica cultural; Canon (Musical form)